Advanced Functional Materials - Tasaltin, Nevin; Sunday Nnamchi, Paul; Saud, Safaa; Tasaltin, Nevin; Sunday Nnamchi, Paul; Saud, Safaa (IntechOpen, 2020)
This book was written by authors in the field of preparation of advanced functional materials and their wide-ranging applications. The topics in the book include: preparation of several advanced functional materials, and their applications in sensors, health, concrete, textile, glasses, and pharmacy. In this book, the authors focused on recent studies, applications, and new technological developments in fundamental properties of advanced functional materials.
English
Keywords: Materials science; Materials science